Laccase in Biorefinery of Lignocellulosic Biomass - Ashutosh Tiwari; Chiu-Wen Chen; Dibyajyoti Haldar; Anil Kumar Patel; Cheng-Di Dong; Reeta Rani Singhania (Applied Sciences, 2023)
Biorefinery has emerged in recent years as an alternative to petrorefinery, as biofuels have all the potential to replace fossil fuels for the sustainable development of human society. From this aspect, lignocellulosic biomasses are the most important, since these are the most abundant ubiquitous most raw material on earth, which can be converted into biofuels such as bioethanol, biobutanol, biohydrogen, biogas, etc. There are several strategies for conversion, such as biochemical, thermochemical, and microbial conversions of biomasses to biofuels; however, each of the strategies has its own consequences. Enzymatic conversion of biomasses into sugars, and thereby into bioethanol, is considered as the most sustainable way. However, biomass recalcitrance to enzymatic hydrolysis is the biggest challenge, as cellulose, hemicellulose, and lignin are intricately attached to each other making their separation a tedious task. Pretreatment is necessary to partially remove or change the form of lignin to make cellulose and hemicellulose accessible to enzymes. Most of the pretreatment methods are designed to target lignin, as it is the major component responsible for recalcitrance nature of biomasses. Laccase is a versatile lignin-degrading or lignin-modifying enzyme which is secreted by filamentous fungi and bacteria, and is reported for the biological pretreatment of biomasses, which is the most sustainable way of pretreatment. However, the rate of the reaction is extremely slow making it less attractive. This article will give an insight into the biorefinery of biomasses, with the special significance to laccase.